First record of the spider genus Wolongia Zhu, Kim & Song, 1997 from India with the description of a new species (Araneae, Tetragnathidae) - Malamel, Jobi J.; Nafin, Karunnappilli Shamsudheen; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2018)
Zhu et al. (1997) erected the tetragnathid genus Wolongia to accommodate Wolongia guoi Zhu, Kim & Song, 1997 and Wolongia wangi Zhu, Kim & Song, 1997 collected from the Sichuan and Shaanxi Provinces in China. In 2009, Ping et al. described Wolongia odontodes from the Gaoligong Mountains and remained with a nominal representation after the erection of the genus. This situation was somewhat rectified by Jin-long Wan & Xian-jin Peng (2013) reporting seven new species from the Gaoligong Mountains (Yunnan Province, southwest China). The genus currently with ten nominal species; three are known only from females, while seven are from both sexes (World Spider Catalog 2017). During our survey in Pathiramanal Island we found an undescribed Wolongia species. This is one of the most diverse areas of the Kerala state of Southern India, situated in the Vembanad Lake, a Ramsar Convention (2013) site (wetland of international importance). In this paper, we describe this new species and provide the first report of Wolongia from India.